Promoting immune defensive responses of epithelial cells in airway disease - Parnham, Michael J.; Norris, Virginia; Kricker, Jennifer A. (Frontiers in Allergy, 2025)
The airway epithelium serves as both a physical barrier and as an active contributor in maintaining immune defense. Upon exposure to external insults such as injury and infection, the epithelium releases alarmins including interleukin-25 (IL-25), IL-33, and thymic stromal lymphopoietin (TSLP), which assist in initiating and amplifying the immune response. Complementing these are the collectins, particularly surfactant protein-D (SP-D), which also participate in the innate immune response. SP-D along with its closely related collectin, SP-A, bind pathogens, apoptotic cells, and allergens, promoting phagocytosis while modulating inflammation and preventing excessive Th2-driven responses. This review discusses the role of the airway epithelium in host defense mechanisms, particularly in chronic obstructive pulmonary disease (COPD) and asthma, and explores the therapeutic implications of epithelial-driven immune responses in respiratory inflammation.